VDBP and VDR Mutations May Cause In-Stent Restenosis - GÜNEY, AHMET İLTER (My University, 2022)
Objective: In-stent restenosis (ISR) is the narrowing of a stented coronary artery lesion. A considerable number of patients undergoing percutaneous coronary intervention (PCI) are affected by ISR. The predominant mechanism in the development of ISR is an inflammatory response to vessel wall injury during PCI. Vitamin D is reported to have anti-inflammatory properties, so it may also be related with ISR. Therefore, in this study the relationship between vitamin D receptor (VDR), vitamin D binding protein (VDBP) gene variations and ISR were investigated.Methods: Fifty-eight ISR patients who have chest pain, underwent angiography and were found to have restenosis in the previously inserted stent were included in the patient group and thirty-five patients who have chest pain and were not found to have restenosis in their previous stent in coronary angiography were included in the control group. rs7041 and rs4588 variations in VDBP; rs1544410 and rs2228570 variations in VDR were investigated by real-time polymerase chain reaction (RT-PCR).Results were evaluated statistically. Results: The CC genotype of rs2228570 variation of VDR and the CA genotype of rs4588 variation of VDBP were found statistically high in patient group. rs7041 variation was found statistically high in patients who had myocardial infarction history before stent implantation. Additionally, it was demonstrated that vitamin D deficiency (vitamin D level<20 ng/ml) was found statistically high in patient group.Conclusion: It was considered that rs2228570, rs4588 variations and the presence of vitamin D deficiency may play role in the formation of ISR.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); ISR; VDR; VDBP; RT-PCR; VITAMIN-D-RECEPTOR; CORONARY-ARTERY-DISEASE; GENE POLYMORPHISMS; ULCERATIVE-COLITIS; D DEFICIENCY; ASSOCIATION; RISK; PROTEIN; ISR; VDR; VDBP; RT-PCR